Evalution of s-scheme iron tungstate/strontium titanate (Fe2WO6/SrTiO3) composite for visible light photocatalysis and antibacterial study - Zhao, Liang (2024)
Discharge of industrial wastewater containing dyes and microorganisms was dangerous to the human health and ecosystem. Multifarious traditional strategies have been adopted for water purification. Heterogeneous photocatalysis was considered as a green and effective technology to solve environmental problems because it only relies on appropriate light to degrade organic contaminants into non-toxic substance or kill most microorganisms. In the present study, the iron tungstate/strontium titanate (Fe2WO6/SrTiO3) composite was prepared by a hydrothermal method and employed in the photodegradation of rhodamine B (RhB) under visible LED light irradiation in 2 h. The prepared photocatalysts were characterized through FESEM, HRTEM, EDX, XRD, FTIR, UV-vis DRS and photoelectrochemical analyses. The Fe2WO6/SrTiO3 composite demonstrated better visible light photoactivity for RhB in comparison with those of pure Fe2WO6 and pure SrTiO3, respectively. The remarkable photoactivity was ascribed to its smaller band gap and effective charge carrier separation. The results of process parameter studies demonstrated that the optimized Fe2WO6 loadings were 20 wt%, photocatalyst dosage were 0.5 g L-1 and operated at pH 12. Besides, the antibacterial properties of the prepared photocatalysts were investigated on the bacteria inactivation towards Escherichia coli (E. coli) and Bacillus cereus (B. cereus). The Fe2WO6/SrTiO3 composite showed the best antibacterial activity as compared to those of pure SrTiO3 and pure Fe2WO6. Moreover, the radical scavenging experiment revealed that holes (h + ), hydroxyl (•OH) and superoxide anion (•O2 - ) radicals were major active radicals in the photocatalytic process. Furthermore, the Fe2WO6/SrTiO3 composite also displayed outstanding recyclability which attained high removal efficiency of 93.9% after five successive runs. Lastly, the optimized photocatalyst was used to degrade the real printed ink wastewater to reveal its potential application in the real wastewater purification. Overall, this study offered a novel Fe2WO6/SrTiO3 photocatalyst that can be applied in degrading the organic contaminants and disinfecting the bacteria in the actual dye-containing wastewater.